Counseling For Teaching Arabic At Schools - Nur Jannah; Nasarudin Nasarudin; Husnan Husnan; Ahmad Helwani; Mujiburrahman Mujiburrahman; Fifi Satrillah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Counseling is assistance services for students both individually and in groups so that they are independent and develop optimally, in personal guidance, social guidance, study guidance, and career guidance, through various types of services and support activities, based on applicable norms. This study aimed to find out the advice and counseling services at schools, to know the direction and counseling service procedures, and to find out what problems students have and how to solve the issues. This type of research is descriptive qualitative research, a method that utilizes qualitative data and is described descriptively. The results of this study are that there are guidance and counseling services for partner schools, which are SDIT Imam Asy-Syafi'i Mataram, MTs Al-Madaniyah, and MTs An-Najah, Indonesia. The issues that arise are that students have difficulty speaking using Arabic, students mishear Arabic utterances because of improper pronunciation, students feel bored in learning because it is difficult to understand, students find it challenging to practice Arabic vocabulary because their original accent is very attached and difficult to change, students have difficulty reading Arabic texts because they do not understand the text and are not fluent in reading Arabic texts, students have problem writing because they are not used to writing Arabic letters. The direction of writing is from right to left because they are used to writing from left to right. Students also often feel shy and insecure when reading Arabic texts or practicing Arabic sentences in front of many people because they fear being wrong. The procedures carried out by the teachers include providing appropriate learning materials to students, providing lots of Arabic practice in learning Arabic, practicing reading aloud to overcome obstacles to reading skills, speaking, and embarrassment in mentioning Arabic sentences. The reading practice also makes it hard to overcome problems with the articulation of words and makes students fluent in pronouncing Arabic sentences. Problems learning Arabic and other issues can be appropriately handled in various ways and methods according to the difficulties experienced by students.